METHODS OF EARLY DIAGNOSIS AND EXAMINATION OF EBSTEIN’S ANOMALY - Ergashov Bekhruzjon Komilovich (TADQIQOTLAR.UZ, 2024)
Abstract: Modern methods of studying the etiology, pathogenesis, clinical course of Ebstein's anomaly, development of modern methods of early diagnosis of Ebstein's anomaly, increasing the level of accuracy in testing methods of Ebstein's anomaly.